Code and Representation of Women in Trans Art Truck Model Roland Barthes Semiotics Studies - Octavhia, Aji Naramita; Santoso, Bernadus Wahyudi Joko (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
Trans art the truck is a specific code that makes the representation of women as objects. The purpose of this study was to analyze the code and the representation of women in trans art contained in the truck bed. This study uses a Roland Barthes semiotic approach as a theoretical approach and a qualitative descriptive approach as a methodological approach. Data collected by the method of documentation and interview method. Data analysis techniques in this study are the meaning of two stages sign of semiotic Roland Barthes. Based on the research found the code contained in the trans art on the tailgate, namely (1) hermeneutics code,  (2) semantics code, (3) symbols code, (4) narrative code, (5) cultural code. In trans art on the tailgate, women represented as (1) women are biological, (2) female praying, (3) tart, (4) female socialites, and (5) sensual woman. The benefits of this research are to give an understanding of the code and representation trans women in art at the tailgate according to semiotic study model of Roland Barthes.